(untitled) (Research, Society and Development, 2025)
Introduction: In the Archaic Period, health was tied to religion, while in the Classical Period, deities of healing and prevention emerged. It evolved into biomedical, procedural, systemic models, and in the 21st century, into integrative medicine, combining conventional and alternative approaches to treat patients holistically. Aim: To conduct a systematic literature review on Integrative Medicine in Brazil, investigating definitions, practices, and implementation challenges. Methods: The review followed PRISMA guidelines. Searches were conducted in SciELO, PubMed, BVS, and Google Scholar, using combined descriptors: ’integrative medicine’, ’well-being’, ’quality of life’, and ’longevity’. A total of 12,618 records were found; 14 studies met inclusion criteria and were fully analyzed. Results: Definitions varied, ranging from complementary and alternative practices to integrated models combining conventional and complementary approaches. A growing emphasis on patient-centered care and evidence-based interventions was noted. Conclusion: Despite conceptual divergence, Integrative Medicine is emerging as a promising health strategy in Brazil, in line with public policies such as the SUS Integrative and Complementary Practices program.